2011
DOI: 10.1007/s13520-011-0011-3
|View full text |Cite
|
Sign up to set email alerts
|

Conservative transformation: actively managed corporate volunteerism in Hong Kong

Abstract: Our Hong Kong-based study used interviews with volunteers and other stakeholders to investigate the perceived integrity and commitment of firms' adoption of actively managed corporate volunteerism (AMCV), to examine whether AMCV was removing barriers against voluntary community service work and to identify volunteers' motives for AMCV involvement. Interviewees perceived that firms were adopting strategically instrumental approaches to AMCV, combining community service provision with corporate image promotion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…At the outset, the students assumed that this would address a genuine need. They related the project plan to the course curriculum as an analogy of how actively managed corporate volunteerism provides opportunities for members of a sponsoring organization (in this case the university) to step out from normal daily work to provide valuable services to those in need (Snell & Wong, 2013). However, the project did not develop as initially conceived.…”
Section: Completing the Road Mapmentioning
confidence: 99%
“…At the outset, the students assumed that this would address a genuine need. They related the project plan to the course curriculum as an analogy of how actively managed corporate volunteerism provides opportunities for members of a sponsoring organization (in this case the university) to step out from normal daily work to provide valuable services to those in need (Snell & Wong, 2013). However, the project did not develop as initially conceived.…”
Section: Completing the Road Mapmentioning
confidence: 99%
“…Although we have shown that support by representatives for stakeholder‐oriented CSR and their adoption of reflexivity vis‐à‐vis government officials are likely to help in the development of co‐operative goals with government units, simply training enterprise representatives without engaging and aligning other employees with congruent CSR policies and practices would constitute opportunistic or ‘window‐dressing ethics’ (Norman and MacDonald ; Sims and Brinkmann ; Snell and Wong ), which is unlikely to be a sustainable strategy. Employee involvement in the design of CSR projects and commitment to participation in them is central to the effectiveness thereof (Gond et al.…”
Section: Practical Implicationsmentioning
confidence: 95%
“…In addition, individuals involved in the same activity may harbour different motivations. Brockner et al (2014) and Snell and Wong (2013) suggest that corporate volunteering can be understood as the employees' participation in activities sponsored by the companies, usually during working hours and for the benefit of some local entity or society, in a broader context in which that organization operates. Usually, the company sponsors a continuous program of community activities and services and offers a platform, where employees and, sometimes, their family members, can take part in such activities.…”
Section: Corporate Volunteeringmentioning
confidence: 99%